Analysis of Initial Nonresponders to Galcanezumab in Patients With Episodic or Chronic Migraine: Results From the EVOLVE‐1, EVOLVE‐2, and REGAIN Randomized, Double‐Blind, Placebo‐Controlled Studies. Issue 2 (21st November 2018) - Nichols, Russell; Doty, Erin; Sacco, Sara; Ruff, Dustin; Pearlman, Eric; Aurora, Sheena K.
Abstract : Objective: To examine the likelihood of response with continued galcanezumab treatment in patients with episodic or chronic migraine without initial clinical improvement. Background: A percentage of patients with migraine may require additional time on pharmacotherapy but discontinue treatment prematurely. Additionally, recognizing when continued treatment is unlikely to provide improvement limits unnecessary exposure. Methods: Post hoc analysis of response after continued galcanezumab treatment was conducted in a subset of patients with episodic (N = 879) and chronic (N = 555) migraine who did not achieve "good" early improvement (episodic, ≥50% reduction in baseline migraine headache days [MHD] and chronic, ≥30% reduction) after 1 month of dosing (NR‐1; episodic, n = 450 and chronic, n = 306). This subset was categorized by level of reduction in MHD during 1 month of treatment: "modest" (>30% to <50% fewer MHD for episodic and >10% to <30% fewer MHD for chronic), "limited" (episodic only; >10% to ≤30% fewer MHD), or "minimal/no" early improvement (≤10% fewer MHD to ≤10% more MHD), or "worsening" (>10% more MHD). The percentages of patients having "better" (≥75% fewer MHD for episodic and ≥50% for chronic), "good, " or "little‐to‐no" (≤10% fewer MHD) response during the remaining treatment period were calculated for each category. Similarly, the subset of NR‐1 patients who did not achieve "good" early improvement after 2 months of treatment (NR‐2; episodic, n = 290 and chronic, n = 240) were categorized by level of their average monthly reduction across 1 and 2 months using similar categories. Results: Of NR‐1 patients with episodic migraine having "modest" early improvement, 62% (96/155) achieved "good" and 20% (31/155) achieved "better" responses with continued treatment. A percentage of patients with "limited" (43%; 46/108) or "minimal/no" (34%; 29/85) early improvement, or "worsening" (20%; 20/102) achieved a "good" response after continued treatment. A percentage of NR‐1 patients with chronic migraine having "modest" early improvement achieved "good" (38%; 44/116) and "better" (13%; 15/116) responses with continued treatment. A "good" response was achieved for a percentage of patients with "minimal/no" early improvement (17%; 23/133). Similar patterns were observed for the NR‐2 subset, though percentages were lower. Conclusions: Galcanezumab‐treated patients with episodic or chronic migraine without response following 1 or 2 months of treatment appear to have a reasonable likelihood of continued improvement in months following initial treatment and this opportunity is more likely in patients showing greater early improvements. While a small percentage of patients with episodic or chronic migraine who experienced worsening in the number of MHD following initial treatment responded with continued treatment, most do not show substantial reduction in MHD. Overall benefit of therapy should be determined collaboratively between the patient and physician.